2019
DOI: 10.1038/s41598-019-53984-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptomics, Proteomics, and Glycomics Reveals the Association between Up-regulation of Sialylated N-glycans/Integrin and Breast Cancer Brain Metastasis

Abstract: Breast cancer brain metastasis has been recognized as one of the central issues in breast cancer research. The elucidation of the processes and pathways that mediate this step will provide important clues for a better understanding of breast cancer metastasis. Increasing evidence suggests that aberrant glycosylation patterns greatly contribute to cell invasion and cancer metastasis. Herein, we combined next-generation RNA sequencing with liquid chromatography-tandem mass spectrometry-based proteomic and N-glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…There is another group of proteins that are detected at the reported subcellular localization but at different MW, such as, BLC-2, RELA, MAPK1, MDM2, TP53, BLNK, SYK, CD19, LYN, ZAP70, PLCG2, suggesting the existence of protein-protein interactions and protein complexes. Thus, this approach is amenable for studying protein interaction networks and/or intracellular signaling dynamic as confirmed previously by our group in this study by correctly identifying the protein players in the previously reported pathways in this B lymphocyte cell line (such as senescence, evading growth suppressors, survival and death pathways, immune system evasion and immunoediting) [26,[63][64][65]. This also opens the possibility to decipher interactions on newly reported pathways such as DAMPs (damageassociated molecular patterns), which might be useful for immunotherapies on lymphoma and leukemia because of their direct relation with the immunogenic cell death (ICD).…”
Section: Discussionsupporting
confidence: 73%
“…There is another group of proteins that are detected at the reported subcellular localization but at different MW, such as, BLC-2, RELA, MAPK1, MDM2, TP53, BLNK, SYK, CD19, LYN, ZAP70, PLCG2, suggesting the existence of protein-protein interactions and protein complexes. Thus, this approach is amenable for studying protein interaction networks and/or intracellular signaling dynamic as confirmed previously by our group in this study by correctly identifying the protein players in the previously reported pathways in this B lymphocyte cell line (such as senescence, evading growth suppressors, survival and death pathways, immune system evasion and immunoediting) [26,[63][64][65]. This also opens the possibility to decipher interactions on newly reported pathways such as DAMPs (damageassociated molecular patterns), which might be useful for immunotherapies on lymphoma and leukemia because of their direct relation with the immunogenic cell death (ICD).…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, elevated sialylation of integrin α6 enhances integrin-mediated cell mobility on collagen and fibronectin in pancreatic cancer cells ( Almaraz et al., 2012 ). More recently, concomitant upregulation of ITGA2 and increased levels of sialylated bi- and tri- antennary N -glycans was correlated with metastatic potential in breast cancer cell lines using glycomics ( Peng et al., 2019 ). It is also reported that α2,6 sialylation is required for the activation of integrin β1 and facilitate its interaction with EGFR, a receptor tyrosine kinase that mediates cell migration and survival signaling ( Hou et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“… Bos et al (2009) showed that ST6GALNAC5 acts as a specific mediator of BCBM by enhancing its adhesion to the brain endothelial cells and facilitating the crossing of the BBB by BC cells. Highly sialylated N-glycans, that were upregulated in the brain-seeking cell line 231BR, are likely to play a crucial role in BCBM, as evaluated using integrated transcriptomics, glycomics, and proteomics ( Peng et al, 2019 ). GABA A receptor alpha3 (GABRA3), normally exclusively expressed in the adult brain, is inversely correlated with BC survival and promotes BC cell invasion and BM by activating the AKT pathway ( Gumireddy et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%